Quality Assurance in Public Vocational Education Institutions - Karakolia, Vasiliki; Vasilopoulos, Andreas (Adult Education Critical Issues, 2025)
This paper examines the perceptions of VET educators with regard to the extant legislative framework for evaluation. Following an overview of the concept of quality, with particular reference to its relationship with evaluation and quality assurance, we examine the manner in which these principles are reflected in the recent legislative framework for Public IEK (DIEK). Subsequently, the findings of a qualitative study conducted with the participation of ten DIEK instructors are presented. The instructors highlight the diverse perceptions of quality among educators in DIEK and also emphasize the challenges associated with adopting different practices, particularly in the context of resistance to change and suspicion regarding the processes involved. Overall, quality assurance is perceived as a complex process, with the trainers’ reservations focusing on the lack of preparation and its implementation in the field.